Media, technology and education in a post-truth society : from fake news, datafication and mass surveillance to the death of trust - Grech, Alex (Digital activism and society., 2021)
This interdisciplinary collection of essays explores the impact of media, emerging technologies, and education on the resilience of the so-called post-truth society. This book explores if a return to civic participation, enhanced critical media literacy, journalism for the public good, techno-interventions and lifelong learning systems can collectively foster a more engaged global citizenry. The post-truth society is associated with a raft of terms that challenge the very notion of what should constitute a democratic and inclusive society: the decline and fall of reason; the disruption of the public sphere; the spread of misleading information; fake news; culture wars; the rise of subjectivity; the co-opting of language; filters, silos and tribes; attention deficits; trolls, polarisation and hyper-partisanship; the conversion of popularity into legitimacy; manipulation by "populist"; leaders, governments, and fringe actors; algorithmic control, targeted messaging and native advertising; surveillance and platform capitalism. The contributions from scholars, technologists, policy-makers and activists raise critical questions about the nature and power of knowledge in the 21st century. Readers are challenged to question their own role in perpetuating certain narratives and to also understand the lived context of people on all sides of a given debate. The diverse perspectives by geography, sector, gender and world-views will widen the appeal of this work to an international audience trying to understand the resilience of the post-truth society.